Induction of Heme Oxygenase-1 with Hemin Reduces Obesity-Induced Adipose Tissue Inflammation via Adipose Macrophage Phenotype Switching - Thai Hien Tu; Yeonsoo Joe; Hye-Seon Choi; Hun Taeg Chung; Rina Yu (Hindawi Limited, 2014)
Adipose macrophages with the anti-inflammatory M2 phenotype protect against obesity-induced inflammation and insulin resistance. Heme oxygenase-1 (HO-1), which elicits antioxidant and anti-inflammatory activity, modulates macrophage phenotypes and thus is implicated in various inflammatory diseases. Here, we demonstrate that the HO-1 inducer, hemin, protects against obesity-induced adipose inflammation by inducing macrophages to switch to the M2 phenotype. HO-1 induction by hemin reduced the production of proinflammatory cytokines (TNF-α and IL-6) from cocultured adipocytes and macrophages by inhibiting the activation of inflammatory signaling molecules (JNK and NF-κB) in both cell types. Hemin enhanced transcript levels of M2 macrophage marker genes (IL-4, Mrc1, and Clec10a) in the cocultures, while reducing transcripts of M1 macrophage markers (CD274 and TNF-α). The protective effects of hemin on adipose inflammation and macrophage phenotype switching were confirmed in mice fed a high-fat diet, and these were associated with PPARγ upregulation and STAT6 activation. These findings suggest that induction of HO-1 with hemin protects against obesity-induced adipose inflammation through M2 macrophage phenotype switching, which is induced by the PPARγ and STAT6 pathway. HO-1 inducers such as hemin may be useful for preventing obesity-induced adipose inflammation.